Sistem Pendukung Keputusan Untuk Penentuan Dosen Favorit Menggunakan Simple Additive Weighting (SAW) - Wowon Priatna; Agung Nugroho; Nurjeli Nurjeli (STIKOM Tunas Bangsa Pematangsiantar, 2019)
The process of determining favorites is what must be in accordance with predetermined criteria. To help in selecting people who deserve to be favorites, a decision support system is needed. One method that can be used to support decisions is to use FMADM (Fuzzy Multiple Addictive Decision Making). Where in this study using the SAW method (Simple Addictive Weighted), which is to find the best alternative from several alternatives. Find the best alternative based on predetermined criteria. This method is chosen to choose the best alternative that is suitable, and look for the value of each attribute, after the search process to get the best.